The Interplay Between Sentiment and MAX: Evidence from an Emerging Market. (August 2021) - Gupta, Nilesh; Jacob, Joshy
Investors with lottery preferences are known to concentrate on stocks with rare but extreme past returns. We investigate the extent to which lottery preference, measured by the MAX variable, varies with the market-wide irrational sentiment. We find that the high-MAX stocks have higher overpricing in a high-sentiment market and earn a lower alpha, compared to the low-sentiment market. Accordingly, the poor returns earned by a long-short portfolio of stocks with extreme MAX values are primarily due to the overvaluation of the high MAX-portfolio during the high sentiment phase. The higher stock volatility in India also magnifies the lottery preference of investors. JEL Classification: G4, G12, G41, G11